Effects of Two Different Specific Neck Exercise Interventions on Palmitoylethanolamide and Stearoylethanolamide Concentrations in the Interstitium of the Trapezius Muscle in Women with Chronic Neck Shoulder Pain. Issue 8 (4th July 2014) - Ghafouri, Nazdar; Ghafouri, Bijar; Fowler, Christopher J.; Larsson, Britt; Turkina, Maria V.; Karlsson, Linn; Gerdle, Björn
Abstract Purpose Chronic neck/shoulder pain (CNSP) is one of the most common pain conditions. The understanding of mechanisms, including the peripheral balance between nociceptive and antinociceptive processes, is incomplete. N‐acylethanolamines (NAEs) are a class of endogenous compounds that regulate inflammation and pain. The aim of this study was to investigate the levels of two NAEs: the peroxisome proliferator‐activated receptor type‐α ligand palmitoylethanolamide (PEA) and stearoylethanolamide (SEA) in the muscle interstitium of the trapezius muscle in women with CNSP randomized to two different neck specific training programs and in a healthy pain‐free control group (CON). Materials and Methods Fifty‐seven women with CNSP were randomized to strength + stretch or stretch alone exercise programs. Twenty‐nine subjects underwent microdialysis procedure before and after 4–6 months of exercise. Twenty‐four CON subjects underwent microdialysis procedure before and after 4–6 months without any intervention in between. Microdialysate samples were collected from the trapezius muscle and analyzed by mass spectrometry for PEA and SEA levels. Results PEA and SEA levels were significantly higher in CNSP patients compared with CON. PEA was significantly higher in CNSP than in CON after both training programs. SEA was significantly higher in CNSP than in CON after stretch alone but not after strength + stretch training. A significant positive correlation was found between changes in pain intensity and in SEA levels in the strength + stretch group, but not in the stretch alone group. Conclusion Our results indicate that exercise interventions differentially affect the levels of the bioactive lipids PEA and SEA in the interstitium of the trapezius muscle in women with CNSP.